Land rental markets and rural poverty dynamics in Northern Ethiopia: Panel data evidence using survival models - Ghebru, Hosaena; Stein, Holden (John Wiley & Sons, 2019)
There is growing interest in understanding the links between land reforms, land markets, and poverty reduction in Africa. The study uses four‐wave panel data from the northern highlands of Ethiopia to assess the dynamics of rural poverty taking into account the status of participation of rural households in the land rental market. Applying both nonparametric (Kaplan–Meier estimator) and semi‐parametric survival models that control for duration dependence of poverty transition, results show participation and degree of participation on the supply side of the tenancy market (landlords) have highly significant and positive effect on the chances of escaping poverty while the same cannot be said about the demand side of the tenancy market (tenants). The empirical evidence also confirms that households headed by older and literate people have relatively larger exit rates from poverty as compared with households headed by younger and illiterate ones. Though transacting farmers may engage themselves in win–win rental arrangements by the time they join the tenancy market, results indicate that gains are unequal as those tenants who enter the markets from low economic leverage (were poor) are liable to face a lower margin of net gains, which may limit their ability to move out of poverty.